2021
DOI: 10.1063/5.0034602
|View full text |Cite
|
Sign up to set email alerts
|

Rich phase transitions in strongly confined polymer–nanoparticle mixtures: Nematic ordering, crystallization, and liquid–liquid phase separation

Abstract: We investigate the rich phase behavior of strongly confined semi-flexible (SFC) polymer–nanoparticle (NP) systems using the graphics processing unit accelerated Langevin dynamics simulation. Hard nanoparticles (HNP) that repel each other and ideal nanoparticles (INP) that do not interact with the same species are used as model additives to a strongly confined semiflexible polymer fluid. Both types of NPs exclude the monomer beads in the same way, but they have qualitatively different effects on the SFC isotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…For tangent hard-sphere chains in the rod limit, the transition occurs at high concentrations, still lower than the solidification of the system [ 106 , 107 ]. Theories have been developed [ 108 , 109 , 110 , 111 ] and studies have been conducted [ 112 , 113 , 114 , 115 , 116 , 117 ] under various conditions on the isotropic-to-nematic transition of semi-flexible chains, as the effect on the nematic order and the phase separation of different types of blends through experimental studies [ 118 , 119 , 120 ] and computer simulations [ 117 , 121 , 122 , 123 , 124 ]. Nguyen et al studied the effect of chain stiffness and temperature on the competition between crystallization and glass formation for unentangled semi-flexible polymer melts [ 85 , 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…For tangent hard-sphere chains in the rod limit, the transition occurs at high concentrations, still lower than the solidification of the system [ 106 , 107 ]. Theories have been developed [ 108 , 109 , 110 , 111 ] and studies have been conducted [ 112 , 113 , 114 , 115 , 116 , 117 ] under various conditions on the isotropic-to-nematic transition of semi-flexible chains, as the effect on the nematic order and the phase separation of different types of blends through experimental studies [ 118 , 119 , 120 ] and computer simulations [ 117 , 121 , 122 , 123 , 124 ]. Nguyen et al studied the effect of chain stiffness and temperature on the competition between crystallization and glass formation for unentangled semi-flexible polymer melts [ 85 , 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…For tangent hard-sphere chains in the rod limit, the transition occurs at high concentrations, still lower than the solidification of the system [78,79]. Theories have been developed [80][81][82] and studies have been conducted [83][84][85][86][87] under various conditions on the isotropic-tonematic transition of semi-flexible chains. Nguyen et al studied the effect of chain stiffness and temperature on the competition between crystallization and glass formation for unentangled semi-flexible polymer melts [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the properties of the LC-host are primarily affected by the geometry of the NPs (size, shape), their bulk and/or surface properties, and their concentration. Over the past two decades, numerous theoretical and experimental studies have been appeared regarding the influence of NPs on phase transitions, orientational order, and the response of the host liquid crystalline matrix to external fields [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Naturally, the well-known Fréedericksz transition has been studied too in certain soft-nanocomposite materials for the voltage threshold of this transition is crucial for applications.…”
Section: Introductionmentioning
confidence: 99%